The effect of Using the Active Learning Strategy on Students' Achievement in the Primary School Stage and their Attitudes in Science Course in the Kingdom of Saudi Arabia - Yousif, Taghreed Mohamed Osman (Journal of Curriculum and Teaching Methodology, 2022)
This study aims to investigate the effect of active learning strategies used in teaching science to primary school students in Hail region, Kingdom of Saudi Arabia. Quantitative research design was used by distributing a questionnaire to the study sample, which is represented by science teachers for the academic year of 2021/2022. The results showed that the mean of the effect of using the active learning strategy on students’ achievement in the primary stage in science in the Kingdom of Saudi Arabia was high (3.67), indicating that active learning increases students’ motivation and facilitates access to useful learning resources, and also has valuable contributions. It also observed that active learning helps achieve learning goals more and enriches teachers’ knowledge and also enhances students’ satisfaction and happiness as well as improves students’ academic performance in science. The results also indicated that the mean of students’ attitudes about the use of active learning for the total degree is (3.65), which is medium, noting that there are some challenges that students face in using the active learning strategy. The study recommends the following: the need to develop students’ capabilities, and train them to optimally use the active learning strategy and student-centered work, move from the circle of negative to positive learning, and conduct several empirical studies that show the effectiveness of employing the active learning strategy in the learning process in the Hail region.
Keywords: active learning strategy; students' academic achievement; students' attitudes; the Kingdom of Saudi Arabia